HIV/AIDS Knowledge Sources of College Student-Athletes in a Southern State - Hunt, Barry P.; Pujol, Thomas J.; Muczko, John P. (My University, 1992)
This study examined the HIV/AIDS-related knowledge of 93 male and female college student-athletes at a DI institution in Louisiana. Knowledge levels are reported according to the ethnicity and gender of the respondents. Significant differences (p<.05) were found between ethnic groups for general knowledge about HIV/ AIDS and between genders for knowledge of disease transmissior methods and risk-reduction techniques. Survey participants indicated mass media, parents, and peers as the most common sources of HIV/AIDS information, and they preferred videos, small group discussions, and classroom lectures as instructional formats. Results may be useful in the development of more effective HIV/AIDS educational initiatives targeting college student-athletes.
Keywords: HIV/AIDS; health